The Dps protein of Salmonella enterica serovar Typhimurium - Sankey, Jennifer T. (Trinity College (Dublin, Ireland). Department of Microbiology, 2008)
As a nucleoid-associated protein, Dps has long been thought to influence gene expression at a global level. In this study the role of Dps in genetic regulation in Salmonella enterica serovar Typhimurium was investigated. Microarray analysis revealed that Dps had little effect on the transcriptional profile of SL1344, few genes responded to its absence. Of the Dps-regulated genes identified one group was involved in amino acid transport and metabolism. Subsequent investigations revealed that Dps has a role to play in the metabolism of SL1344 particularly in stationary phase.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin